2006
DOI: 10.1158/1055-9965.epi-06-0344
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparity in the Relationship between Obesity and Plasma Insulin-Like Growth Factors: The Multiethnic Cohort

Abstract: Previous studies on the relationship between obesity and circulating insulin-like growth factor (IGF) hormones show inconsistent findings and have not considered the possibility of racial/ethnic -specific differences that may exist. We therefore examined the relationship between obesity status [as measured by body mass index (BMI)] and plasma levels of the IGF proteins, IGF-I, IGF-binding protein 3 (IGFBP-3), and the molar ratio of IGF-I/IGFBP-3 in Whites, African Americans, Latinos, Japanese Americans, and Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 21 publications
2
27
1
Order By: Relevance
“…Although differing associations of body mass index with IGFs among ethnic groups Table 2. Age-adjusted ORs and 95% CIs for prostate cancer risk in relation to prediagnostic IGF-I, IGFBP-3, and IGFto-IGFBP-3 ratio All (N = 512) Blacks (n = 153) Whites (n = 184) Asians (n = 175) may affect results (21), in our population no clear patterns were observed. Although we did not observe differences in the risk relationships associated with ethnicity, caution is required in interpretation due to small numbers for subgroup analyses.…”
Section: Discussioncontrasting
confidence: 54%
“…Although differing associations of body mass index with IGFs among ethnic groups Table 2. Age-adjusted ORs and 95% CIs for prostate cancer risk in relation to prediagnostic IGF-I, IGFBP-3, and IGFto-IGFBP-3 ratio All (N = 512) Blacks (n = 153) Whites (n = 184) Asians (n = 175) may affect results (21), in our population no clear patterns were observed. Although we did not observe differences in the risk relationships associated with ethnicity, caution is required in interpretation due to small numbers for subgroup analyses.…”
Section: Discussioncontrasting
confidence: 54%
“…This finding suggests that increases in postmenopausal estrogen levels, as occurs with increasing BMI, may not have as much effect on breast cancer incidence in Black women. In the same cohort, levels of plasma insulin-like growth factor I, which is part of the pathway for negative feedback on growth hormone secretion, declined with increasing BMI in Latinas, Japanese, and White women, but increased with increasing BMI in African American women (48). Insofar as growth hormone plays a role in the etiology of breast cancer, the differing relation of obesity to insulin-like growth factor-I levels by ethnic group may explain the relative lack of association of obesity with breast cancer risk in postmenopausal Black women.…”
Section: Discussionmentioning
confidence: 91%
“…The mechanisms underlying the potential interactions of DM and high-grade disease with race and obesity remain unclear. A prior study found that overweight and obese CM had lower free IGF-1 levels than all AAM, regardless of obesity status, and non-obese CM [24]. Moreover, obese CM have lower levels of testosterone than all AAM, regardless of obesity status, and non-obese CM [25].…”
Section: Discussionmentioning
confidence: 91%